PERBEDAAN POLA BERAT BADAN BAYI YANG DIBERI ASI EKSKLUSIF DAN YANG TIDAK DIBERI ASI EKSKLUSIF DI POSYANDU DESA GAYAMANÂ KECAMATAN MOJOANYARMOJOKERTO - Mustika Sari, Surya (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Exclusive breastfeeding is a gift to the baby only breast milk for 6 months without the additional of other liquids such as infant formula, juice, honey, tea and water, and without the additional of solid foods, like bananas, milk porridge, biscuits, rice and rice porridge team, except vitamin , minerals, and medications. But until now there are many mothers who do not understand about the importance of exclusive breastfeeding for infants, especially for the babys weight. The purpose of this study was to determine the weight of babies who were exclusively breastfed, weight babies who are not breastfed exclusively and differences in patterns of weight babies who were breastfed exclusively and not exclusively breast-fed at the Posyandu Gayaman Mojoanyar District of Mojokerto city. This design of this study a comparative analytic. The population in this study were as many as 54 respondents, the samples used were 24 respondents to exclusively breast-fed infants and 30 respondents for infants who are not breastfed exclusively breast-fed way of uptake, carried out by total sampling technique. The data results showed no difference between the weight of babies who were exclusively breastfed and not breastfed exclusively, on the observation sheet shows 20 babies out of 24 respondents who were breastfed exclusively have increased weight, while infants who are not breastfed exclusively found only 10 infants from 30 infants who gain weight and 8 baby lost weight. From the results of research conducted, it can be concluded that there are many babies who are exclusively breastfed should be nourished in the actual intake of other not yet the time given. Efforts made by local village midwife is improving education and counseling on exclusive breastfeeding in infants is also useful especially for weight loss, of course, by the method attractive and easy to understand language the parants of respondents.Keywords: Patterns of body weight, breast-fed infants exclusive, not exclusively breast-fed